Attractiveness of protected areas for geotourism purposes from the perspective of visitors: the example of Babiogórski National Park (Poland) - Widawski Krzysztof (Open Geosciences, 2018)
This article examines the tourist role of protected areas important for their unanimated nature potential. In Poland the highest form of legal protection is a national park. Babiogórski National Parks is one of 23 national parks in Poland. The aim of this article is to present its tourist attraction based on its geotourist potential considered by tourists who visit this park. At the beginning a brief history of protection of Babia Góra is presented. Based on stock-taking sightseeing method an analysis of the most important tourist attractiveness elements (like infrastructure or tourist values) is done. The focus on the values of unanimated nature is made grouping them into four main categories. As the result of research on infrastructure the most important accommodation units were indicated present at the surroundings of this National Park which is vital for its tourist capacity. For the correct functioning of tourist movement at the protected area the supporting infrastructure is important bearing a lot of functions. The function of channeling of the tourist movement as well as the didactic function are the most important for protection and correct use of geotourist values. Among the many elements of the supporting infrastructure the most important ones are tourist and didactic routes (their course and themes are presented). The most important part of the article is the presentation of the participants of the tourist movement opinions on the Babiogórski National Park tourist attractiveness. A survey was conducted and then analysed on 308 respondents in 2011. They were asked to judge both the quality of infrastructure as well as attraction of geotourist values together with their adaptation to reception by the tourist movement. The results analysis served as a base to appraise the state and perspectives for the geotourism development in Babiogórski National Park from the point of view of the receivers of tourist product i.e. the protected area.